0584 Self-Reported Daytime Sleepiness in Obstructive Sleep Apnea Patients Relates to Insomnia and Depression Symptoms. (12th April 2019) - Dubrovsky, Boris; Weingarten, Jeremy A; Cunningham, John; Lopez, Rieza; Leung, Jonathan
Abstract: Introduction: Insomnia is often co-morbid with OSA, although daytime sequelae, such as sleepiness, may differ. As each disorder is associated with depression, depressive symptoms may contribute to the subjective manifestation of sleepiness. Presently, Epworth Sleepiness Scale (ESS) is analyzed as a function of PSG variables, insomnia and depressive symptoms in a large, ethnically diverse sample of OSA patients. Methods: Before the in-lab PSG, 960 patients (18-97y.o., 520 women) completed ESS (normal range<9), Insomnia Severity Index (ISI, normal range<8), and Center for Epidemiologic Studies Depression Scale-Revised (CESDR, normal range<16). ESS scores were regressed on age, sex, BMI, PSG variables meeting the criterion of p<0.1 when entered alone, ISI, CESDR, ISIxAHI and CESDRxAHI interactions. Results: Group means: AHI=27.2±33.2 (635 patients had OSA, AHI≥5); ESS=8.8±5.9; ISI=13.0±7.0; CESDR=14.4±12.6. The model included total sleep time (TST), N2%, sleep latency (SL), REM latency (REML) respiratory arousal index (RespAr), AHI, and time below 80% SpO2 (tO2<80). As both ISIxAHI and CESDRxAHI interactions were significant (p<0.001, p=0.002, respectively), the model was run separately for four OSA groups (AHI<5.0, 5.0≤AHI<15.0, 15.0≤AHI<30.0, AHI≥30.0). Predictors of higher ESS were: in no-OSA group, shorter SL (p=0.011, R 2 =2.5%), shorter REML (p=0.022, R 2 =2.0%), higher RespAr (p=0.036, R 2 =1.7%), higher ISI (p<0.001, R 2 =5.4%), and higher CESDR (p=0.015, R 2 =2.2%); in mild-OSA group, higher ISI (p=0.054, R 2 =1.8%), and higher CESDR (p<0.001, R 2 =8.0%); in moderate-OSA group, lower TST (p=0.006, R 2 =6.3%), shorter SL (p<0.001, R 2 =10.5%), higher RespAr (p=0.006, R 2 =6.2%), higher ISI (p=0.058, R 2 =3.0%), and higher CESDR (p=0.054, R 2 =3.1%); and in severe-OSA group, shorter SL (p=0.006, R 2 =3.5%) and higher ISI (p<0.001, R 2 =13.9%). Four OSA groups accounted for a small yet significant portion of ESS variance (ESS means: 8.2±5.4, 8.9±5.6, 8.5±5.8, 9.6±6.5, respectively, F(3, 938 df)=4.3, p=0.005, R 2 =1.4%). Conclusion: While OSA severity alone had only a small contribution to self-reported sleepiness, effects of insomnia and depression symptoms depended on the OSA level. In mild OSA, depressive symptomatology was the best predictor of ESS, while in severe OSA it was insomnia symptomatology. PSG variables were strongest predictors of ESS in moderate OSA. Support (If Any): None.